Being friendly: paced mating for the study of physiological, behavioral, and neuroplastic changes induced by sexual behavior in females - Ventura-Aquino, Elisa; Paredes, Raúl G. (Frontiers in Behavioral Neuroscience, 2023)
Paced mating in rats is an experimental condition that allows the evaluation of sexual behavior in a way that closely resembles what occurs in seminatural and natural conditions enabling the female to control the rate of the sexual interaction. In conventional non-paced mating tests, females cannot escape from male approaches, which may lead to an unrewarding overstimulation. Paced mating is an alternative laboratory procedure that improves animal welfare and has a higher ethological relevance. The use of this procedure contributed to the identification of physiological and behavioral factors that favor reproduction. Paced mating includes motivational and behavioral components differentiating quantitative and qualitative characteristics that are critical for the induction of the rewarding properties of mating. These positive consequences ensure that the behavior will be repeated, favoring the species' survival. Sexual reward is an immediate consequence of paced mating, mediated mainly by the endogenous opioid system. Paced mating also induces long-lasting neuroplastic changes, including gene expression, synthesis of proteins, and neurogenesis in sex-relevant brain areas. The interest in paced mating is growing since the complexity of its elements and consequences at different levels in a laboratory setting resembles what occurs in natural conditions. In this review, we analyze the classic studies and recent publications demonstrating the advantages of using paced mating to evaluate different aspects of sexual behavior in females.